The Modification and Performance of a Large Animal Anesthesia Machine (Tafonius®) in Order to Deliver Xenon to a Horse - Santangelo, Bruna; Robin, Astrid; Simpson, Keith; Potier, Julie; Guichardant, Michel; Portier, Karine (Frontiers in Veterinary Science, 2017)
Introduction Xenon, due to its interesting anesthetic properties, could improve the quality of anesthesia protocols in horses despite its high price. This study aimed to modify and test an anesthesia machine capable of delivering xenon to a horse. Materials & methods An equine anesthesia machine (Tafonius, Vetronic Services LTD, UK) was modified by including a T-connector in the valve block to introduce xenon, so that the xenon was pushed into the machine cylinder by the expired gases. A xenon analyzer was connected to the expiratory limb of the patient circuit. The operation of the machine was modelled and experimentally tested for denitrogenation, wash-in and maintenance phases. The system was considered to consist of two compartments, one being the horse’s lungs, the other one being the machine cylinder and circuit. A 15 year-old, 514 kg, healthy gelding horse was anaesthetized for 70 minutes using acepromazine, romifidine, morphine, diazepam and ketamine. Anesthesia was maintained with xenon and oxygen, co-administered with lidocaine. Ventilation was controlled. Cardiorespiratory variables, expired fraction of xenon (FeXe), blood gases were measured and xenon was detected in plasma. Recovery was unassisted and recorded. Results FeXe remained around 65 %, using a xenon total volume of 250 L. Five additional boli of ketamine were required to maintain anesthesia. PaO2 was 45 ± 1 mmHg. The recovery was calm. Xenon was detected in blood during the entire administration time. Conclusions This pilot study describes how to deliver xenon to a horse. Although many technical problems were encountered, their correction could guide future endeavors to study the use of xenon in horses. □